International Migration Opportunities and Occupational Choice: A Case Study of Philippine Nurses 2002 to 2014 - Mary P. Arends-Kuenning; Alvaro Calara; Stella Go (Institute for the Study of Labor (IZA), 2015)
We analyze trends in nursing education in the Philippines during a period of rising and falling demand for Philippine nurses in the developed countries. Based on focus group discussion data obtained in the Philippines, we examine students' motivations to become nurses and to what extent their choices were affected by the possibility of international migration. The number of nursing graduates rose, resulting in brain gain. However, policies promoting the migration of skilled workers such as nurses impose high costs on middle class and lower class families who invest in education hoping that a family member will be able to migrate.
Keywords: F66; I11; J24; J44; 330; brain drain; brain gain; international nurse migration; Philippines